Pengaruh Komunikasi Pada Hubungan Partisipasi Penyusunan Anggaran Dengan Kinerja Manajerial PT. (Persero) Angkasa Pura I Bandar Udara Ngurah Rai - Bali - Lestari, Komang Ratih Komala; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 2 No 1 (2013), 2013)
Purpose of this study was to determine the effect of budget participation on managerial performance and the effect of communication on the relationship of  budget participation with managerial perfomance PT. AP I Ngurah Rai – Bali. Samples were obtained by using the method of census. Hypothesis testing using model regression ordinary least square with one independent variable and regression moderation. The analysis shows that budget participation significantly affect to improve managerial perfomance, communication capable of moderating significantly in relationship of budget participation with managerial perfomance, thus communication is moderating variable. Keywords: managerial perfomance, communication, budget participation